Srednjeveški Blejski otok v arheoloških virih = Medieval archaeology of Bled Island - Štular, Benjamin (Opera Instituti Archaeologici Sloveniae, 2020)
The book Medieval Archaeology of Bled Island is presenting the results of a state-of-the-art archaeological analysis of data from archaeological excavations of the 1962 and 1964.